Students' Morals Development Through Habitation Method In Kindergarten (TK) Aisyiyah Bustanul Athfal 2 Mataram - Hafiz, Abdul; Zaenudin, Zaenudin; Anggeraini, Hani; Fitriah, Nurul; Rafa Hidayat, Muhammad Yusuf (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The results of observations conducted by the Community Service Team at Aisyiyah Bustanul Athfal 2 Kindergarten Mataram in moral development through habituation are still not effective in being implemented; there are still some students who are disobedient, challenging, and showing disruptive behavior towards their friends. For this reason, the purpose of this service is to provide Moral Development in Early Childhood Through the Habituation Method at Aisyiyah Bustanul Athfal 2 Kindergarten, Mataram. The service method uses a participatory approach, namely an approach that actively involves all related parties, including teachers, parents, and students. The results of this community service activity show that the implementation of moral development in early childhood through the habituation method has a significant positive impact on student behavior at Aisyiyah Bustanul Athfal 2 Kindergarten, Mataram. The habituation program in the form of greetings, queuing, helping each other, and praying before and after activities has succeeded in increasing children's discipline, politeness, and empathy. Qualitative and quantitative evaluations confirmed the consistency of ongoing behavioral changes, as quantitative data from observation sheets showed an average increase of 35–50% in observed behavioral indicators.